The Practice of Architectural Design Competition in Indonesia: Whose Interests Are Served? - Joko Adianto; Rossa Turpuk Gabe (International Journal of Built Environment and Scientific Research, 2018)
Architecture Design Competition (ADC) has been acknowledged as one of the prominent methods to serve the best of public interest. However, the spatial infringements frequently occur as the indication of the incompatibility between the best results and the needs of the users. A multi-stages qualitative research was done, in Jatinegara Vertical Rent Housing as a selected case study, and aimed to identify the incompatibility. The disproportion of the available time with the required outputs emerges as the scapegoat of the capitulation of criticality to overcome the incompatibility. Moreover, the exclusion of the designated users in the whole stages of ADC is the essential cause, as an embodied misconception of the definition client-user in the professional practice. The finding of this research addresses several recommendations to reclaim the criticality in ADC and save the practice of this profession from the mortifying failure to serve the best public interest.